2017
DOI: 10.1111/aogs.13271
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes in primiparous women–impact of age and adiposity: a register‐based cohort study

Abstract: The prevalence of GDM is high in primiparous women. Both age and degree of adiposity influenced the risk for GDM. To reduce GDM risk, adiposity should be prevented already in childhood and primiparity should be encouraged at a younger age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
5
30
0
1
Order By: Relevance
“…The high incidence of GDM in our Brazilian cohort is not surprising. In a recent study conducted in Finland, 16.5% of the nulliparous women evaluated were diagnosed with gestational diabetes [10]. This result is in line with our findings, but lower rates have also been reported.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The high incidence of GDM in our Brazilian cohort is not surprising. In a recent study conducted in Finland, 16.5% of the nulliparous women evaluated were diagnosed with gestational diabetes [10]. This result is in line with our findings, but lower rates have also been reported.…”
Section: Discussionsupporting
confidence: 92%
“…However, the prevalence of overweight and obesity epidemic in women of childbearing age contributes to a higher risk of GDM [20,[21][22][23][24]. Only few studies have actually reported risk factors for GDM in nulliparous women [10][11][12]25]. In Brazilian nulliparous women, these risk factors have still not been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study period, between the years 2009 and 2015 in Finland, the nationwide incidence of GDM, including both primiparous and multiparous women, increased from 9% to 16% . Our study observation of a high GDM incidence is in line with nationwide data, as well as with previous findings from the same study cohort . The comprehensive screening for GDM according to the Finnish Current Care Guidelines for GDM since 2008 probably explains our high incidence of GDM in these primiparous Finnish women .…”
Section: Discussionsupporting
confidence: 91%
“…Hyperglycemia in pregnancy (HGiP) is a major cause of complications in pregnancy. The growing rates of obesity, polycystic ovary syndrome (PCOS), and advanced maternal age in women of childbearing age have contributed to the increased prevalence of HGiP . Changed diagnostic pathways and more stringent diagnostic criteria have also led to a substantial increase in the number of women diagnosed with HGiP …”
Section: Introductionmentioning
confidence: 99%